2008
DOI: 10.1007/s10151-008-0440-8
|View full text |Cite
|
Sign up to set email alerts
|

Local gentamicin reduces perineal wound infection after radiotherapy and abdominoperineal resection

Abstract: Based on the results of this study, we recommend local application of gentamicin in the sacral cavity in patients who undergo abdominoperineal resection after shortterm radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 21 publications
2
52
0
1
Order By: Relevance
“…In the presented study, GCCI implantation enabled shorter systemic antibiotic therapy and quicker hospital discharge. These results are similar to those in other fields, especially in gastrointestinal surgery, where GCCI proved to reduce the length of hospital stay by 40% [12]. The benefit was more pronounced in high infection risk procedures.…”
Section: Discussionsupporting
confidence: 87%
“…In the presented study, GCCI implantation enabled shorter systemic antibiotic therapy and quicker hospital discharge. These results are similar to those in other fields, especially in gastrointestinal surgery, where GCCI proved to reduce the length of hospital stay by 40% [12]. The benefit was more pronounced in high infection risk procedures.…”
Section: Discussionsupporting
confidence: 87%
“…The skin was closed with a double layer of resorbable suturesPatients stratified by type of procedure Colonic resection Reversal of Hartmann procedure Abdominoperineal resection (APR) Subtotal colectomy Low anterior resection n  = 221 total patients n  = 107 gentamicin collagen implant plus ceftriaxone + metronidazole IV or gentamicin + metronidazole IV (Group I) n  = 114 ceftriaxone + metronidazole IV or gentamicin + metronidazole IV (Group II) Wound infections :Group I: 5.6% (6/107) vs.Group II: 18.4% (21/114) ( P  < 0.01) LOS : Group I: 13.8 days vs. Group II: 16.3 days ( P  = 0.015) Microbiology : Bacterial species were cultured from n  = 3/107 in group I and n  = 8/114 in group IIGrüssner (2001) [27]Level 1Septocoll ® Three implants 5 × 8 cm evenly inserted into the sacral cavity at one level with the remnants of the levator ani musclePatients undergoing abdominoperineal resection (APR) for low rectal carcinoma n  = 97 total patients n  = 49 gentamicin collagen implant plus cefazoline + metronidazole plus sacral drainage (Group I) n  = 48 cefazoline + metronidazole plus sacral drainage (Group II) Wound infections :Group I: 6.1% (3/49) vs. Group II: 20.83% (10/48) ( P  < 0.05) Wound healing : Primary perineal wound healing—Group I: 88% (43/49) vs. Group II: 75% (36/48) ( P  = 0.12)Secondary perineal wound healing with infection—Group I: 6% (3/49) vs. Group II : 21% (10/48) ( P  < 0.05) Microbiology :Bacteriologic efficacy in Group I: 83.7% (41/49) vs. Group II: 60.4% (29/48) ( P  = 0.013)Nowacki (2005) [26]Level 1Collatamp ® One 10 × 10 cm implant placed in the presacral area below the peritoneal reflection. When anterior resection was performed, the implant was wrapped around the anastomosisPatients undergoing Anterior resection Low anterior resection Abdominoperineal resection (APR) Hartmann procedure n  = 229 randomised n  = 113 gentamicin collagen implant plus metronidazole + cefuroxamine IV (Group I) n  = 116 metronidazole + cefuroxamine IV (Group II) Early post - operative complications (30   days) : Total complications—Group I: 20.7% (22/106) vs. Group II: 37.5% (42/112) ( P  = 0.0441)Surgery > 3 h—Group I: 19.2% (15/78) vs. Group II: 40.8% (31/76) ( P  = 0.0314)Intraoperative bowel perforation/contamination of peritoneal cavity—Group I: 20% (3/15) vs. Group II: 57.9% (11/19) ( P  = 0.01) Cancer recurrence : Local recurrence/or metastasis at 36 months—Group I: 14.4% vs. Group II: 32.3% ( P  = 0.03)Rate of local recurrence similar in both groupsDistant metastasis—Group I: 10.3% vs Group II: 28.1% ( P  = 0.0095) Survival : 3-year survival—Group I: 88.66% vs. Group II: 73.96%de Bruin (2008) [28]Level 3Collatamp ® Three implants inserted into the sacral wound cavity at one level with the remnants of the levator ani muscleConsecutive series of patients undergoing abdominoperineal resection (APR) for rectal cancer after short-course radiotherapy n  = 40 total n  = 19 gentamicin collagen implant plus amoxicillin + clavulanate IV plus sacral drainage (Group I) n  = 21 amo...…”
Section: Methodsmentioning
confidence: 99%
“…The results of the study showed that GCI reduced the incidence of postoperative perineal and sacral infections. In a retrospective study conducted by de Bruin et al [13], three GCI have been inserted in the same place, but another medical product was used (Collatamp®). All patients underwent short-term radiotherapy followed by abdominoperineal resection.…”
Section: Discussionmentioning
confidence: 99%